Communication Gap: A Case Study on the Use of Indonesian and English by International Students at IPB University Bogor - solihin, olih; Ahmad Zakki Abdullah; I Nyoman Aji Suadhana Rai; Hasibullah Atiqi (Mandala: Jurnal Ilmu Hubungan Internasional, 2024)
This study focuses on the challenges faced by international students at IPB University Bogor in using a mixed language, namely English and Indonesian, in both academic and social contexts. The aim of the research is to understand how the use of mixed language affects communication and social interaction among foreign students from Afghanistan, Pakistan, and Ghana at IPB University. The research method employed is qualitative analysis based on in-depth interviews with these students. The findings indicate that the use of mixed language creates confusion and difficulties in maintaining smooth communication, impacting their academic participation and social interactions. The foreign students demonstrated effective adaptation strategies, such as simplifying language and seeking social support. In conclusion, cross-cultural communication challenges require additional support and better adaptation strategies. Developing intercultural competence, including language skills, social skills, adaptive attitudes, and emotional competence, as well as institutional support, is crucial to enhancing the experience of international students in a multicultural environment